Propriedades vibracionais de cristais de valina e ácido glutâmico monohidratado na forma dl - Paiva, Fernando Martins de (2017)
This work aims at vibrational and structural characterization of amino acids valine (C5H11NO2) and glutamic acid monohydrate (C5H9NO4.H2O), both in DL-form. Crystals of these amino acids were grown by the slow evaporation method using water as solvent. For the verification of the structure of both samples we proceeded the realization of X-ray diffraction experiments, at ambient conditions, and Rietveld refinement. Raman and infrared spectroscopy experiments were realized at ambient conditions and the classification of vibrational modes for both crystals was proposed. In order to study the stability of the structure of these two amino acids were realized X-ray diffraction, Raman and infrared spectroscopy, and thermal analysis of DSC and TG in function of the temperature. Results of Raman and infrared spectroscopy were realized showed that the structure of the DL-valine is stable at high temperature until the occurrence of its decomposition at 473 K also verified in the TG/DSC experiments. The diffraction pattern of DL-glutamic acid monohydrate crystals presented changes in peaks between 248 and 313 K and, from 373 K, began the dehydration of the structure, in concordance with the TG/DSC experiments. At 398 K the structure is completely dehydrated. At low temperatures the stability of the structure of DL-valine was verified by experiments of Raman spectroscopy since the temperature of 300 down to 42 K, and infrared, of 300 down to 80 K. Modifications in the modes corresponding to the rocking of the unit, r(CO2), what drives us to believe that this crystal suffers a conformational phase transition at low temperatures. As for the crystals of DL-glutamic acid monohydrate, were performed Raman spectroscopy experiments, at low temperatures, in two orientations, in the first from 300 to 13 K and, in the second, form 295 to 12 K and in the infrared the amino acid was subjected to temperature variations between 300 and 80 K. Also were made measures of X-ray diffraction between ambient temperature and 83 K. Continuous changes in the diffraction pattern, as well as in the number of vibration modes indicate that the structure of this amino acid suffer a structural transition between 284 e 203 K.